2011
DOI: 10.1002/tox.20713
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic and immunologic effects of perinatal exposure to the brominated diphenyl ether (BDE) mixture DE‐71 in the Sprague‐Dawley rat

Abstract: Brominated diphenyl ethers (BDEs) are persistent environmental contaminants found in human blood, tissues, and milk. To assess the impact of the commercial BDE mixture DE-71 on the developing immune system in relation to hepatic and thyroid changes, adult (F0) rats were exposed to DE-71 by gavage at doses of 0, 0.5, 5, or 25 mg/kg body weight (bw)/d for 21 weeks. F0 rats were bred and exposure continued through gestation, lactation and postweaning. F1 pups were weaned and exposed to DE-71 by gavage from postna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…Several in vivo rodent studies have pointed towards a thyroid hormone disturbance after PBDE-exposure, where lowered concentrations of T4 were the most frequent and significant finding [28;29;5255]. Three of six studies found no changes in T3 levels in mice and rats [28;29;54], three studies measured TSH [28;54;55] where only one found an effect, and only in male rats [55].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vivo rodent studies have pointed towards a thyroid hormone disturbance after PBDE-exposure, where lowered concentrations of T4 were the most frequent and significant finding [28;29;5255]. Three of six studies found no changes in T3 levels in mice and rats [28;29;54], three studies measured TSH [28;54;55] where only one found an effect, and only in male rats [55].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, experimental data using animal models strongly suggested the occurrence of PBDE immunotoxicity, manifested as altered splenic lymphocyte populations, increased susceptibility to infections, and the release of pro-inflammatory cytokines (Zhong et al, 2011;Pellacani et al, 2012;Bondy et al, 2013). However, the data on PBDE immunotoxicity are still limited, and the mechanism(s) remains largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although some animal models have reported weight gain with PBDE exposure (Bondy et al 2013; Dufault et al 2005; Fernie et al 2006; Gee and Moser 2008; Suvorov et al 2009), others have indicated null or inverse associations (Daubié et al 2011; Ta et al 2011; Talsness et al 2008). One possibility is that the direction of the association between PBDEs and growth measures differs between species.…”
Section: Discussionmentioning
confidence: 99%
“…Their ability to persist, bioaccumulate, and biomagnify has resulted in chronic and prolonged exposure despite the voluntary cessation of penta- and octaBDE manufacturing in the United States in 2004. PBDEs have been associated with weight gain in animal studies (Bondy et al 2013; Dufault et al 2005; Fernie et al 2006; Gee and Moser 2008; Suvorov et al 2009). PBDEs have been reported to increase adipocyte differentiation, decrease glucose oxidation, disturb glucose homeostasis, and alter gene expression in the metabolic pathways by directly interacting with retinoic X receptor (RXR), a key regulatory transcription factor in the adipogenic pathway in vertebrates (Bastos Sales et al 2013; Hoppe and Carey 2007; Kamstra et al 2014; Suvorov and Takser 2010; Tung et al 2014).…”
Section: Introductionmentioning
confidence: 99%